Nonstructural barriers to adult vaccination - T. Mark Doherty; Fiona Ecarnot; Jacques Gaillat; Lois Privor-Dumm (Taylor & Francis Group, 2024)
ABSTRACTAdult vaccination coverage remains low, despite vaccine recommendations, improved access, and reimbursement. Low vaccination coverage and an aging population at higher risk from vaccine-preventable diseases lead to preventable disability and deaths, straining healthcare systems. An Advisory Board meeting was, therefore, held to identify non-structural barriers to adult vaccination and discuss potential solutions to increase uptake. Many non-structural factors can influence vaccine uptake, such as heterogeneity in the population, (fear of) vaccine shortages, incentives, or mandates for vaccination, understanding of disease burden and personal risks, time and opportunity for healthcare providers (HCPs) to discuss and deliver vaccines during general practice or hospital visits, trust in the health system, and education. To address these barriers, push-pull mechanisms are required: to pull patients in for vaccination and to push HCP performance on vaccination delivery. For patients, the focus should be on lifelong prevention and quality of life benefits: personal conversations are needed to increase confidence and knowledge about vaccination, and credible communication is required to build trust in health services and normalize vaccination. For providers, quality measurements are required to prioritize vaccination and ensure opportunities to check vaccination status, discuss and deliver vaccines are not missed. Financial and quality-based incentives may help increase uptake.